Dark angel [large type] - Andrews, Brian, 1973-; Wilson, Jeffrey, 1963- (Andrews, Brian, 1973- Shepherd series, 2022)
"Former Navy SEAL Jedidiah Johnson returns to Nashville ready to begin his training with the elite warriors known as the Shepherds. He thinks he knows what to expect when he arrives on the sprawling, state-of-the-art facility but quickly realizes he'll have to find his place as the rookie leader of a new team. Then he starts having visions of an imminent attack overseas, and with the clock ticking, Jed and his team are dispatched to neutralize the threat. All the while, Jed hears whispers of another threat . . . a name that raises unexplained fear and anger throughout the Shepherds organization. Once a military man, Nicholas Woland betrayed the Shepherds and all they stood for when he joined their enemies. After years in prison, Woland is eager to get back in action spreading chaos and death. And he has been freed for a purpose: a sinister plot that will result in hundreds of casualties and incite worldwide religious warfare for years to come. As Woland and the Shepherds race toward a collision, Jed must rely on his gifts, his training, and his untested team to make critical decisions on a global stage--never realizing that a secret servant of the enemy is growing closer and closer to him."--